PENERAPAN TEKNOLOGI NEAR FIELD COMMUNICATION (NFC) DALAM PEMBAYARAN PREMI ASURANSI - Sasa Marissa; Reihan Mahendra; Silviani Pulungan; Dini Vientiany (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Near field communication (NFC) is a technological innovation that is very instrumental in connecting between devices to other devices. This device only requires a minimum of 2 devices in the form of a signal catcher and transmitter. Not only that, this feature also does not require an internet network connection so that it can be used anywhere and anytime. The NFC feature was first present on Nokia phones which at that time Android and Iphone users were not as popular as today's times. But there is an interesting thing that the first Nokia to use NFC was not Nokian but on the Panasonic P506iC cellphone which was launched in 2004. Since then, NFC has grown rapidly and been integrated into a variety of modern devices. The use of NFC is not limited to data transfer between phones, but is also applied in various applications, such as digital payments, access control, and inventory tracking. The main advantage of NFC is its ability to perform secure and fast wireless communication by simply bringing two compatible devices closer to each other. Going forward, NFC technology is expected to continue to evolve and offer more innovations that can make everyday life easier, including integration with the Internet of Things (IoT), which allows household and industrial devices to communicate with each other seamlessly.